The Impact of Coffee and Caffeine on Health and the possibilities of their supplementation for different populations- a narrative review - Palak, Andrzej Palak; Gabriela Grylowska; Marcin Rebizant; Agata Żak; Anna Ignatowicz; Anna Paluch; Katarzyna Gunia; Mateusz Banasik; Michał Tryba; Aleksandra Adamczyk (Quality in Sport, 2026)
Background. Caffeine is the most widely consumed psychostimulant in the human diet, found in over 60 plant species and ingested mainly through coffee, tea, and soft drinks. Many people perceive caffeine as unhealthy, yet growing evidence suggests moderate intake carries substantial benefits across multiple disease domains, though it has not been systematically considered as a clinical supplement. Aim. To synthesize evidence on the health effects of caffeine and coffee and evaluate the feasibility of recommending supplementation as a preventive or adjunctive measure for specific patient populations. Material and methods. A literature search was performed using PubMed and Google Scholar, focusing on conditions most common in today’s society. We prioritised meta-analyses, prospective cohort studies and RCTs, supplemented by governmental and NGO sources for statistics and policies. Results. Consumption of 2–5 cups of coffee per day was consistently associated with reduced all-cause mortality, lower risk of several cancers, and cardiovascular diseases. A linear inverse relationship was observed between intake and type 2 diabetes risk, also noted for decaffeinated coffee. Caffeine was associated with reduced Parkinson’s disease risk and slower progression. Moderate intake of 3–5 cups appeared to lower depression risk, more strongly in women, and 2–3 cups daily was linked to reduced dementia risk and better cognitive outcomes, again more prominently in women. Conclusions. Clinicians should consider integrating caffeine and coffee into preventive care discussions, accounting for contraindications, sleep disturbances, and dependence risk. Supplementation may benefit those at elevated risk of cardiovascular disease, type 2 diabetes, certain cancers, Parkinson’s disease, depression, and dementia, particularly women and older adults. Further RCTs are needed to establish precise dosing guidelines.